The Role of Early Life Experience and Species Differences in Alcohol Intake in Microtine Rodents - Anacker, Allison M. J.; Ahern, Todd H.; Young, Larry J.; Ryabinin, Andrey E. (PLOS ONE, 2012)
Social relationships have important effects on alcohol drinking. There are conflicting reports, however, about whether early-life family structure plays an important role in moderating alcohol use in humans. We have previously modeled social facilitation of alcohol drinking in peers in socially monogamous prairie voles. We have also modeled the effects of family structure on the development of adult social and emotional behaviors. Here we assessed whether alcohol intake would differ in prairie voles reared by both parents compared to those reared by a single mother. We also assessed whether meadow voles, a closely related species that do not form lasting reproductive partnerships, would differ in alcohol drinking or in the effect of social influence on drinking. Prairie voles were reared either bi-parentally (BP) or by a single mother (SM). BP- and SM-reared adult prairie voles and BP-reared adult meadow voles were given limited access to a choice between alcohol (10%) and water over four days and assessed for drinking behavior in social and non-social drinking environments. While alcohol preference was not different between species, meadow voles drank significantly lower doses than prairie voles. Meadow voles also had significantly higher blood ethanol concentrations than prairie voles after receiving the same dose, suggesting differences in ethanol metabolism. Both species, regardless of rearing condition, consumed more alcohol in the social drinking condition than the non-social condition. Early life family structure did not significantly affect any measure. Greater drinking in the social condition indicates that alcohol intake is influenced similarly in both species by the presence of a peer. While the ability of prairie voles to model humans may be limited, the lack of differences in alcohol drinking in BP- and SM-reared prairie voles lends biological support to human studies demonstrating no effect of single-parenting on alcohol abuse.